Impact of rural residence and low socioeconomic status on rate and timing of prenatal detection of major congenital heart disease in a jurisdiction of universal health coverage. (1st September 2022) - Kaur, A.; Hornberger, L. K.; Fruitman, D.; Ngwezi, D.; Eckersley, L. G.
ABSTRACT: Objective: Socioeconomic status (SES) and distance of residence from tertiary care may impact fetal detection of congenital heart disease (CHD), partly through reduced access to and quality of obstetric ultrasound screening. It is unknown whether SES and remoteness of residence (RoR) affect prenatal detection of CHD in jurisdictions with universal health coverage. We examined the impact of SES and RoR on the rate and timing of prenatal diagnosis of major CHD within the province of Alberta in Canada. Methods: In this retrospective study, we identified all fetuses and infants diagnosed with major CHD in Alberta, from 2008 to 2018, that underwent cardiac surgical intervention within the first year after birth, died preoperatively, were stillborn or underwent termination. Using maternal residence postal code and geocoding, Chan SES index quintile, geographic distance from a tertiary‐care fetal cardiology center and the Canadian Index of Remoteness (IoR) were calculated. Outcome measures included rates of prenatal diagnosis and diagnosis after 22 weeks' gestation. Risk ratios (RR) were calculated using log‐binomial regression and stratified by rural (≥ 100 km from tertiary care) or metropolitan (< 100 km from tertiary care) residence, adjusting for year of birth and the obstetric ultrasound screening view in which CHD would most likely be detected (four‐chamber view; outflow‐tract view; three‐vessel or three‐vessels‐and‐trachea or non‐standard view; septal view). Results: Of 1405 fetuses/infants with major CHD, prenatal diagnosis occurred in 814 (57.9%). Residence ≥ 100 km from tertiary care (adjusted RR, 1.19; 95% CI, 1.05–1.34) and higher IoR (adjusted RR, 1.9; 95% CI, 1.1–3.3) were associated with missed prenatal diagnosis of major CHD. Similarly, residence ≥ 100 km from tertiary care (adjusted RR, 1.41; 95% CI, 1.22–1.62) and higher IoR (adjusted RR, 3.6; 95% CI, 2.2–8.2) were associated with prenatal diagnosis after 22 weeks. Although adjusted and unadjusted analyses showed no association between Chan SES index quintile and prenatal‐diagnosis rate overall nor for residence in rural areas, in metropolitan regions, lower SES quintiles were associated with missed prenatal diagnosis (quintile 1: RR, 1.24; 95% CI, 1.02–1.50) and higher risk of diagnosis after 22 weeks' gestation (quintile 1: RR, 1.46; 95% CI, 1.10–1.93; quintile 2: RR, 1.66; 95% CI, 1.24–2.23). Conclusions: Despite universal healthcare, rural residence in Alberta is associated with lower rate of prenatal diagnosis of major CHD and higher risk of late prenatal diagnosis (≥ 22 weeks). Within metropolitan regions, lower SES impacts negatively prenatal‐diagnosis rate and timing. © 2022 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Bebbington. Click here to view the Editorial.